Hybrid governance structures in brazilian and canadian credit cooperatives networks from the perspective of the transaction costs theory - Arruda, Alessandro Gustavo Souza; Faria, Ana Cristina de; Romeiro, Maria do Carmo; Fernandes, Francisco Carlos (Revista de Administração da UFSM, 2018)
This paper aims at building a theoretical model that characterizes the influence of Hybrid Governance Structures (HGS) in Transaction Costs (TC) of credit cooperatives networks in Brazil and Canada. From the characterization of the variables that influence the TC, it’s possible to perform a discrete analysis of hybrid forms of governance which is characteristic of strategic networks of credit cooperatives canadian Desjardins and brazilian Sicredi. The case studies analysis proved that the evolution of HGS was simultaneous with the evolution of the legal and institutional environment, in a dialectical process. However, one can see that while evolving from different legal and institutional environments, there is a tendency to homogeneity in these networks, at least in the creation of ad hoc institutions to deal with the most significant TC. An equation was inferred at the final section of the work, to perform the comparison of the costs of HGS with the transaction of financial intermediation of credit cooperatives networks. The model can be used to compare the analysed TC with the correpondent costs of lean financial institutions. According to this equation, the cost to carry out internal transactions to the network, in addition to the costs arising from the political and social pressures present in this type of institution, must be less than or equal to TC of financial institutions with hierarchical governance structures. This not only corroborates the discriminating alignment hypothesis of Williamson (2005), but adds elements for classification and analysis of these costs.